Wanprestasi dalam Perjanjian Pinjam Meminjam Uang pada PT. PNM Mekaar (Studi di Kelurahan Sei Putih Barat Kota Medan) - Azzahra Lubis, Adibah; Syuhada Lubis, Mhd. Teguh Syuhada Lubis (UNES Law Review, 2024)
A money lending and borrowing agreement is an agreement that must be agreed upon by the parties, as well as with PNM Mekaar and customers in Sei Putih Barat Subdistrict, Medan City. Customers who want to borrow money are required to make an agreement that has been made by PNM Mekaar. Of course, there are customers who make loans who default, so this must of course be resolved because it has become an obligation that must be fulfilled. The purpose of this research is to find out agreements for borrowing and borrowing money, to find out the forms of default committed by customers, and to find out the settlement of defaults from PNM Mekaar in Sei Putih Barat Subdistrict, Medan City for customers who make defaults. The method used is to combine normative juridical and empirical juridical. The research results state that the customer must agree to the agreement that has been provided, the contents of the agreement are in the form of obligations that must be fulfilled and the agreement must be agreed upon by the group leader and the person in charge. The form of default that occurred to PNM Mekaar customers, West Sei Putih Village, Medan City, was not making payments on time and there were customers who ran away. The resolution of the default carried out by PNM Mekaar, Sei Putih Barat Subdistrict, Medan City, was to implement a joint and several responsibility payment system, and the group leader tried to find and contact the person in charge of the member who had run away.